A intensificação da mercantilização da educação superior no Brasil: a particularidade dos Cursos Irregulares de Serviço Social nos Estados da Paraíba, Pernambuco e Ceará - Silva, Maria Carolina Nascimento (2020)
The present dissertation, entitled: “THE INTENSIFICATION OF THE MERCANTILIZATION OF HIGHER EDUCATION IN BRAZIL: the particularity of irregular Courses in Social Work the States of Paraíba, Pernambuco and Ceará”, presents the results obtained from the research carried out on the intensification of the commodification of education higher from irregular courses in Social Work, with cuts in the States of Paraíba, Pernambuco and Ceará. The general objective is to analyze the intensification of the mercantilization of higher education taking as reference the contemporary crisis of capital and its consequences expressed in the counter-reform of the State. The sustained assumption in the investigation is that this intensification has an impact on the professional training of Social Work at a private level, with the offer of irregular courses, whose tendency is the lateralization of the ABEPSS Curricular Guidelines of 1996. To reach this conclusion, we start from the debate on the capitalist crisis as a concrete materiality of the object of study, guided by the neoliberal fundomonetation adjustment, the counter-reform of the State and the commercialization of higher education that impacts professional training in Social Work as a socially determined process. It is a qualitative and quantitative study, carried out through bibliographic and documentary analysis. The documentary research was based on the analysis of the Internal Administrative Processes and Conclusive Opinions referring to graduates from irregular courses, who presented themselves at the Regional Social Service Councils of Paraíba, Pernambuco and Ceará, between the years 2016-2019. Therefore, our theoretical methodological choice answers our specific objectives from three chapters. The first chapter focuses on the study of the contemporary crisis of capital and its consequences expressed in the counter-reform of the State and in the commercialization of Higher Education. The second chapter is dedicated to apprehending the historical process of Social Work, highlighting the ABEPSS Curricular Guidelines of 1996 and the tendency to commercialize professional training. The third and last chapter focuses on the exposure of research data, seeking to verify the incidences and impacts of commercialization on professional training in Social Work from irregular Social Work courses. The research will point out in the final considerations that the crisis and the capital restructuring measures require a reconfiguration of education that are carried out through counter-reforms. That the Brazilian State acts in accordance with the dictates of international organizations, facilitating the commercial expansion of higher education. That irregular courses in Social Work appear as a result of the intensification of this commercialization and contributes to the hegemonic dispute in the profession between the critical and conservative perspective.